Studies on Biodegradation of waste polyethylene - Awasthi, Shraddha (My University, 2018)
This insistent human pursuits for improvement of living standards such as mining and extraction of minerals and oils have enhanced the environmental pollution several folds. However, the waste generated from such industries are toxic and carcinogenic, having detrimental effect on the environment and human health. the apposite management of such waste in one the most serious issues confronted by environmentalists currently. Several physical, chemical and biological methods have been approached to degrade these pollutants from the solid waste. Among these, biological degradation has been adapted as most propitious techniques for the degradation of these polyethylene pollutants.
Keywords: Studies; Biodegradation; Waste Polyethylene